IDENTIFIKASI JENIS DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN RUANG TERBUKA PUBLIK TEMPORER (Studi Kasus: Solo Car Free Day di Jalan Slamet Riyadi, Kota Surakarta) - , RARAS WIDO PINANDHE, Widyasari Her Nugrahandika S.T, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Today, the existence of public space is getting reduced due to the dominance of privat area. However, it now appears the car free day as a strategy providing new public space. One of the organizers is the city of Surakarta. In the city of Surakarta, the event called Solo Car Free Day and held in two locations. Uniquely Solo Car Free Day on Slamet Riyadi street is more crowded than the Solo Car Free Day in Juanda street. In addition to the enthusiasm of people on Solo Car Free Day is greater than the public space other Surakarta. This study aims to identify the type of use and the factors that affect people's enthusiasm in using the Solo Car Free Day on Jalan Slamet Riyadi. This study uses qualitative and inductive approach performed in Solo Car Free Day to explain phenomena in Solo Car Free Day. Sampling was conducted using purposive sampling and accidental sampling method followed by the various stakeholders who totaled 29 respondents. Primary data were collected through observation and interviews, while secondary data collection is done by searching the related data in the relevant institutions. Data analysis was done through the preparation phase followed by a unit of information on a theme grouping. This study concluded that Solo Car Free Day is a public space which become a multifunctional space, but not inconsistent to the theme administration. In addition, the utilizations cause environmental problems. Utilization of space due to internal factors and external factors. Internal factors consist of: 1) management, 2) accesibility, and 3) the magnetic activity. While external factors such as community pride against Solo Car Free Day or can be called by Topohilia (Tuan, 2011).